The ubiquity of arts in virtual environments of contemplation: immersing in the Pinacoteca of Sao Paulo - Batista Lima, Fabio Rogerio [UNESP]; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2018)
The continuous technological changes directly affect labor relations, family, community, in which the place and space stop being concrete and absolute and become, according to Zygmunt Bauman, liquids and relatives. This article aims to study the Pinacoteca arts museum of Sao Paulo based on the heuristics of the Pervasive Information Architecture (AIP). The research is theoretical, descriptive and exploratory, and was based on the qualitative systematic observation of the collected bibliography. As a result, we conclude that the heuristics Architecture of Pervasive Information (API) can provide support in the praxis for future elaborations of Architecture of Pervasive Information directed to virtual environments of contemplation of arts.
Keywords: Museum; Architecture of Information; Pervasive Information Architecture (AIP); Ubiquity; Heuristics